Media Pembelajaran Aksara Jawa untuk Anak Sekolah Dasar Menggunakan Augmented Reality - Hanif, Rifqi Fadhlurrahman; Avianto, Donny (Teknik Informatika Universitas Pamulang, 2024)
Learning the Javanese script used in the Javanese language is challenging, especially for those who are just starting to learn the language. Students and the general public rarely use or are interested in Javanese script because of its difficulty. In order to protect the local language, researchers came up with the idea of teaching Javanese script to students, especially students who are just starting to learn in elementary school. This is done by creating a learning media application that is interesting, easy to understand, and entertaining. This Javanese script learning application is made using Augmented Reality (AR) technology and penanda-based tracking mechanism. This program is a learning tool that can turn 2D objects into 3D objects and bring the virtual world into the real world because it uses Augmented Reality technology. When used with the app's quiz feature, this educational tool can help elementary school students to improve their memory and skills, as well as inspire them to learn more through engaging instructions. The app was tested through blackbox testing to demonstrate its feasibility, with 100% successful results for all intended buttons and functions. AR camera distance testing resulted in a 90% success rate in detecting penandas at a certain distance.